2010
DOI: 10.1007/s11125-010-9144-8
|View full text |Cite
|
Sign up to set email alerts
|

Creating effective Holocaust education programmes for government schools with large Muslim populations in Sydney

Abstract: Holocaust education can play a role in countering the ongoing problem of prejudice and incitement to hate that can lead to racial tension and violence. This article examines the beliefs of Muslim school children towards Jews in Sydney, Australia. It then discusses efforts to use Holocaust education to combat racist beliefs and hate language, and an alternative approach that illustrates the common values in the Abrahamic faiths. The article analyzes the advantages and disadvantages of using various school progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…We do not know how the teachers implemented the curriculum, nor how students interpreted it (Bromley and Russell, 2010). As noted above, previous research has shown that sometimes there is a disconnect between what is taught in the classroom and what is learned at home (Rutland, 2010). In addition, teachers are not receiving adequate and consistent training in how to effectively and sensitively present this subject (Nägel, et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We do not know how the teachers implemented the curriculum, nor how students interpreted it (Bromley and Russell, 2010). As noted above, previous research has shown that sometimes there is a disconnect between what is taught in the classroom and what is learned at home (Rutland, 2010). In addition, teachers are not receiving adequate and consistent training in how to effectively and sensitively present this subject (Nägel, et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…While they each offered an interesting interpretation, looking at the Holocaust through the perspective of religious teaching would benefit from exploring more angles, such as sharing an Islamic response to the question of God's power and goodness. Interfaith dialogue and reflection on the Holocaust could allow for the exploration of common moral values inherent in the three major monotheistic religions of Islam, Christianity, and Judaism (Rutland, 2010). In addition, religious education classes could provide a suitable opportunity to discuss the Arab-Israeli conflict, including how the tension between the two groups impacts the understanding of why and how the Holocaust happened (Schechter and Salomon, 2005;Porat, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is envisioned that the important "moral, social and spiritual" values taught (Ibid, 10) will lead students to gain insights and make informed choices when confronted with injustice in our modern world (Salmons 2003). According to Rutland (2010), Holocaust education "can provide an important educational framework to promote…positive interfaith and interethnic relations" (75)…given that teachers are aware of suitable Holocaust teaching material and the emotional needs and reactions of their students. It is not only a moral obligation to remember and teach the Holocaust, but also a tribute to the 1,500,000 children (similar in age to the students being taught), who lost their lives in this historic genocide.…”
Section: Why Teach the Holocaust?mentioning
confidence: 99%